Emerging microbiome-directed therapies in inflammatory bowel disease: beyond diet modification and FMT - Quiroga Centeno, Andrea; Atanasova, Konstantina; Ebert, Matthias; Thomann, Anne K.; Reindl, Wolfgang (Seminars in immunopathology, 2025)
Inflammatory bowel disease (IBD) is a multifactorial and heterogeneous disorder that remains challenging to manage. Growing evidence implicates the gut microbiome as a key player in IBD pathogenesis, with many patients displaying intestinal dysbiosis that can drive aberrant immune responses. Traditional microbiome-targeted interventions, such as dietary modifications, probiotics, and fecal microbiota transplantation (FMT), have yielded mixed and often temporary benefits in IBD. This shortcoming of broad-spectrum approaches underscores the need for more precise, personalized strategies that account for each patient’s unique microbiota and disease phenotype. Recent advances in omics and bioengineering have catalyzed the development of emerging microbiome-directed therapies that move beyond these broad approaches. This narrative review highlights emerging microbiome-directed therapies that aim to restore gut homeostasis and mitigate inflammation in IBD. We critically evaluate the rationale and therapeutic potential of rationally designed bacterial consortia and genetically engineered bacteria, which represent next-generation probiotics tailored to complement deficient microbial functions or deliver anti-inflammatory agents in situ. We also expand the discussion to underexplored microbiome constituents - archaea, protists, bacteriophages, and fungi - highlighting their roles in IBD and potential as therapeutic targets. Finally, we discuss the key advances and ongoing challenges of these innovative approaches, from ecological stability and engraftment to safety and regulatory considerations.
Online veröffentlicht: 25. November 2025
Gesehen am 26.01.2026